2004
DOI: 10.1098/rspb.2004.2885
|View full text |Cite
|
Sign up to set email alerts
|

The origins of intensive marine fishing in medieval Europe: the English evidence

Abstract: The catastrophic impact of fishing pressure on species such as cod and herring is well documented. However, the antiquity of their intensive exploitation has not been established. Systematic catch statistics are only available for ca.100 years, but large-scale fishing industries existed in medieval Europe and the expansion of cod fishing from the fourteenth century (first in Iceland, then in Newfoundland) played an important role in the European colonization of the Northwest Atlantic. History has demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(149 citation statements)
references
References 23 publications
(22 reference statements)
4
137
0
Order By: Relevance
“…This ability is particularly relevant because these data reflect sustained continuous harvesting of herring populations for millennia before more than a century of modern industrial exploitation. Similar to historical research on the impacts of early industrial-era fishing on Atlantic cod (84) and herring in northern Europe (85,86), and the long-term effects of human use of coral reefs (87), the archaeological analyses synthesized here critically extend the temporal depth of ecological baselines for contemporary fisheries management.…”
Section: Lowmentioning
confidence: 62%
“…This ability is particularly relevant because these data reflect sustained continuous harvesting of herring populations for millennia before more than a century of modern industrial exploitation. Similar to historical research on the impacts of early industrial-era fishing on Atlantic cod (84) and herring in northern Europe (85,86), and the long-term effects of human use of coral reefs (87), the archaeological analyses synthesized here critically extend the temporal depth of ecological baselines for contemporary fisheries management.…”
Section: Lowmentioning
confidence: 62%
“…Extensive fishing of the Icelandic cod stock started as early as the thirteenth century [23], and previous studies have suggested that historical fisheries affected the Atlantic cod stock [21,34,70]. Although the total catches of historical fishing fleets are difficult to estimate, historical documents refer to multiple fleets of up to 500 English and Dutch long liners fishing simultaneously in Icelandic waters in the sixteenth century [71].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests an earlier drop of 2-38C in summer temperatures in the thirteenth century and subsequent decrease in sea temperatures in the fourteenth and fifteenth centuries [38][39][40]. Climate change and the concomitant ecosystem effects may have determined Atlantic cod catches both in historical [21] and modern times [41]; for example, temperatures warmer than at present are expected to be favourable for cod recruitment around Iceland [42].…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of some well-studied species such as cod (Gadus morhua), haddock (Melanogrammus aeglefinus) and plaice (Pleuronectes platessa) (see Eero, 2012;Pope and Macer, 1996;Rijnsdorp and Millner, 1996;Rose, 2004), the time series data on catch and effort needed to assess the level of exploitation and trends in stock biomass are generally available for only a few decades (FAO, 2011). Since man has been fishing the seas for centuries (Barrett et al, 2004;Hoffman, 2005;Lotze, 2007;Fromentin and Powers, 2005), fish stocks and ecosystems may already have been heavily affected before systematic data collection started. Therefore, it seems worthwhile to investigate whether other sources of information could throw light on the historic developments in fisheries and in the state of fish stocks and marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%